087 A novel comparison of impact accelerations between prospectively injured runners and runners with and without a history of injury. (3rd March 2020) - Burke, Aoife; Moran, Kieran; Whyte, Enda; Dillon, Sarah; Gore, Shane; O'Connor, Siobhán
Abstract : Background: While ground reaction force (GRF) impact loading has been hypothesized as an aetiological factor of running injuries, research findings are conflicting. Recently, impact accelerations have grown in favour because of their advantages over force plate GRFs (e.g., low cost, portable), especially in measuring segment-specific loading. Objective: To compare differences in peak tibial impact accelerations (Peakaccel ) and rate of acceleration (Rateaccel ) between runners who have never been injured (INJ0 ) with runners who have sustained a prospective injury (INJP ), and those with a retrospective injury history (INJR ). Design: Prospective and retrospective cohort study. Setting: Laboratory based testing. Patients (or Participants): As part of a larger prospective study, 24 INJ0 were matched by gender (14 M, 10 F), age, years running experience and cumulative mileage to 24 INJP and 24 INJR runners during a 1 year surveillance period. Interventions (or assessment of risk factors): Tibial Peakaccel and Rateaccel were measured using tri-axial accelerometers over 10 strides of running on a treadmill at a self-selected pace. Injuries were tracked over a 1 year period. Main outcome measurements: We hypothesized that tibial Peakaccel and Rateaccel would be greatest in INJP when compared to INJ0 and INJR runners. Results: A two-way between-groups ANOVA [sex by injury status] indicated no significant interaction effects of sex and injury status on Peakaccel or Rateaccel . However, a significant main effect was found for injury status on Rateaccel (F: 4.43, p: 0.02, η 2 : 0.125), with a Tukey post hoc analysis indicating significant differences between INJP and INJ0 (p: 0.01). Rateaccel : INJP 679.4 m/s 3 > INJR 510.8 m/s 3 > INJ0 407.9 m/s 3 . Conclusions: Rateaccel at the tibia may be an important metric to explore in running-injury prevention strategies. This novel study also indicates the value of exploring loading/impact accelerations in both INJ0 and INJp runners.